Tracing the Sphinx from symbol to specters: reflections on the organization of geographies of concern. Issue 3 (4th May 2021) - Riad, Sally; Jack, Gavin
ABSTRACT: The concept of the gaze plays an important role in (post)colonial organizational analysis. It addresses dynamics of looking and being seen, particularly as they pertain to knowledge and identity. Drawing on Derrida's writing on spectrality as it intersects with text and aesthetics, we chart a theoretical framework with which we broaden and deepen extant approaches to the gaze. We illustrate its organizational dynamics across two vignettes that examine writing on the Sphinx by Hegel and Mark Twain. Our work broadens the literature on the gaze with a new view on the (re)production of presence and absence. It also deepens reflection by outlining how the occupation of concern is shaped by interested blindness and unease at a gaze from a specter. These insights invite reconsideration of extant views on knowledge and identity within (post)colonial organizational analysis and inspire reflection on how scholars can participate in tracing the organization of geographies of concern.